You are on page 1of 31

: )(

) (-:

.
Principles of Probability

. .
.
. .
... .

.
.
.
.
.
.

) (- : Random Experiment :

:
. .
. .
. .

) (- )( : Sample Space :

.
S ). n(S

. S

):(-

:
. .
. .

- -

: )(

:
. :
H : T
H T S = {H , T} :

. n(S) = 2 :
. :

H : T
:
)(H,H), (H,T), (T,H), (T,T
:
})S = {(H,H), (H,T), (T,H), (T,T
n(S) = 4 :
:

}S = {H,T} {H,T
})= {(H,H), (H,T), (T,H), (T,T
) ( n(S) = 2 2 = 4

):(-
:
. .
.
:

. :
1 : 2 3 4 5 6 :
} S = {1, 2, 3, 4, 5, 6 . n(S) = 6 :
. :

. () :
) ( ) (:
: :
- -

: )(

}S={1,2,3,4,5,6}{1,2,3,4,5,6
={(1,1),(1,2),(1,3),(1,4),(1,5),(1,6),(2,1), (2,2), (2,3), (2,4), (2,5), (2,6),
(3,1),(3,2),(3,3),(3,4),(3,5),(3,6),(4,1), (4,2), (4,3), (4,4), (4,5), (4,6),
})(5,1),(5,2),(5,3),(5,4),(5,5),(5,6),(6,1), (6,2), (6,3), (6,4), (6,5), (6,6
) ( n(S)=66=36 :
: :

: ) (:

)(6,6
)(6,5
)(6,4
)(6,3
)(6,2
)(6,1
6

)(5,6
)(5,5
)(5,4
)(5,3
)(5,2
)(5,1
5

)(3,6
)(4,6
)(3,5
)(4,5
)(3,4
)(4,4
)(3,3
)(4,3
)(3,2
)(4,2
)(3,1
)(4,1
3
4

)(2,6
)(2,5
)(2,4
)(2,3
)(2,2
)(2,1
2

)(1,6
)(1,5
)(1,4
)(1,3
)(1,2
)(1,1
1

6
5
4
3
2
1

:
) (4,3 ) (4,3
. (4,3)S ) (4,3 4 3

) (3,4 3
4 .
) (- : Event :

. S

A . A S

A . A

- -

: )(

(Impossible Event) . S
.

(Sure Event) . S S

A ) . n(A A
. A

):(-


. S


n(A) = 3

AS

;} } = {2, 4, 6 { = A

n(B) = 3

BS

;} } = {1, 3, 5 { = B

n(C) = 5

CS

;} } = {1, 2, 3, 4, 5 { = C

n(D) = 1

DS

;} } = {6 { = D

n() = 0

;} { = } { =

n(S) = 6

SS

;} } = {1, 2, 3, 4, 5, 6 { = S

. A B C
:D
S

- -

: )(

:
} A={2,4,6 2 4
. 6

} D={6 . 6

):(-


:
} { = A

} { = B

} { = C

S ={(H,H),(H,T),(T,H),(T,T)}; n(S)=4
A = {(H,H),(H,T)}; n(A) = 2
B = {(T,H),(T,T)}; n(B) = 2
C = {(H,H),(H,T),(T,H)}; n(C) = 3

):(-

) (x ) (y :
}x+y <4
}x=y
} x =5
} x+y =1

- -

A = { (x,y):
B = { (x,y):
C = { (x,y):
D = { (x,y):

: )(

:
)(6,6
)(1,6) (2,6
)(3,6
)(4,6
)(5,6
)(6,5
)(1,5
)(2,5
)(3,5
)(4,5
)(5,5
)(6,4
)(1,4
)(2,4
)(3,4
)(4,4
)(5,4
)(6,3
)(1,3
)(2,3
)(3,3
)(4,3
)(5,3
)(2,2
)(3,2
)(4,2
)(6,2
)(1,2
)(5,2
)(3,1
)(4,1
)(6,1
)(1,1
)(2,1
)(5,1

A
C
;})A = { (x,y): x + y < 4 } = {(1,1), (1,2), (2,1
n(A)=3
B = { (x,y): x = y } = {(1,1),(2,2),(3,3),(4,4),(5,5),(6,6)} ; n(B)=6
C = { (x,y): x =5 } = {(5,1),(5,2),(5,3),(5,4),(5,5),(5,6)} ; n(C)=6
;D = { (x,y): x+y =1 } = { } =
n(D)=0
) (- ) (: Algebra of Events :

.
.
)( Union :

A B AB
A B . AB
A B A B.

} xB AB = {x S: xA

)( Intersection :
A B AB AB
A B . AB A
B .

- -

: )(

} xB AB = {x S: xA

)( Complement :
A AC A
. A A A
.

} A = AC = {x S: xA

)n(A ) = n(S) n(A


C

)( : Difference between Two Events :


A B AB
A . B AB

A . B

} xB AB = {x S: xA

:
C C

(A ) = A
SC =
C = S
AC = SA
AA = A
AA = A
AS = A
AS = S
A =

- -

: )(

A = A
AB AB = A
AB AB = B

:
C

AB = AB

: :
C
C
(A B) = A B
C
C
C
(A B) = A B
):(-
C

.
. .
. :

= A

= B
= C .
. :
AB, AC, A B , (A B)C, ABC
:
C

. :
S ={(H,H,H),(H,H,T),(H,T,H),(H,T,T),
})(T,H,H),(T,H,T),(T,T,H),(T,T,T
:
n(S) = 2 2 2 = 23 = 8
.
})A={(H,H,H),(H,H,T),(H,T,H),(H,T,T
n(A) =4
B={(H,H,H),(H,H,T),(H,T,H),(H,T,T),
})(T,H,H),(T,H,T), (T,T,H
n(B) =7
})C={(T,H,H), (T,T,H
n(C) =2

- -

: )(

.
})A={(H,H,H), (H,H,T), (H,T,H), (H,T,T
})B={(H,H,H), (H,H,T), (H,T,H), (H,T,T), (T,H,H), (T,H,T), (T,T,H
})C={(T,H,H), (T,T,H
})AC = {(T,H,H),(T,H,T),(T,T,H),(T,T,T
})BC = {(T,T,T
;}) AB = {(H,H,H), (H,H,T), (H,T,H), (H,T,T
n(AB) = 4
;}) AC = {(H,H,H), (H,H,T), (H,T,H), (H,T,T), (T,H,H), (T,T,H
n(AC)=6
C
C
}) A B = {(T,H,H),(T,H,T),(T,T,H),(T,T,T)} {(T,T,T
; })= {(T,H,H),(T,H,T),(T,T,H),(T,T,T
C
n(A BC) = 4
C
; }) (A B) = {(T,H,H),(T,H,T),(T,T,H),(T,T,T
n((A B)C) = 4
C
; AB = A B =
n(ABC) = 0
)(Disjoint (Mutually Exclusive) Events :
A B . AB=

. .

AB =

AB

Exhaustive Events :
A1,A2,,An ) (
. :

= A1 A2 An = S
- -

Ai
i =1

: )(

:
:
. } A = {2, 4, 6 } B = {1, 3, 5:
. AB :
:

. AB={1, 2, 3, 4, 5, 6} = S

. } A1={1,2,3 } A2={2,3,4 } A3={3,4,5,6


.

) ( : Equally Likely Outcomes :




) ( .
) (H ) . (T
1
2 3 4
5 . 6

) (
.
) (-: Probability :
) (

. .
Probability of An Event :

A ) P(A A
. .

- -

: )(

Classical Definition of Probability :



) n(S A :
)n(A
A
= )P(A
=
)n(S
S
):(-
)-
.(


n(S)=6 :

P(A) = n(A)/n(S) = 3/6 =0.5


P(B) = n(B)/n(S) = 3/6 =0.5
P(C) = n(C)/n(S) = 5/6 =0.8333
P(D) = n(D)/n(S) = 1/6 =0.1667
P() = n()/n(S) = 0/6 =0.0
P(S) = n(S)/n(S) = 6/6 = 1.0

n(A) = 3
n(B) = 3
n(C) = 5
n(D) = 1
n() = 0
n(S) = 6

}A = {2, 4, 6
}B = {1, 3, 5
}C = {1, 2, 3, 4, 5
}D = {6
}{=
}S = {1, 2, 3, 4, 5, 6

):(-
) (- :
:


n(S)=4 :

n(A) = 2
P(A) = n(A)/n(S) = 2/4 =0.5
n(B) = 2
P(B) = n(B)/n(S) = 2/4 =0.5
n(C) = 3
P(C) = n(C)/n(S) = 3/4 =0.75
- -

})A = {(H,H),(H,T
})B = {(T,H),(T,T
})C = {(H,H),(H,T),(T,H

: )(

:
.

.

.
: Relative Frequency Probability

n A

) rn(A A
:
)rn (A
n

lim

= )P(A

)rn (A

n
A
A n

.
:
A .
1000 ) rn(A
. n .
:
)rn (A
= 0.5
n

lim

= )P(A) = P(H

- -

: )(

:


n .
.
.
.
) (- )( : Axioms of Probability :
S ) P(.

S ) P(A A
AS :

. AP(A) 0 :
P(S) = 1 .
. A1, A2, A3, )( ) (
Ai Aj = ij:

- -

: )(


) P A i = P(A i
i =1 i =1

P(A1 A2 A3 ) = P(A1) + P(A2 ) + P(A3) +

) (
.
.
:

. :
.

P() = 0
A1, A2, , An )( :

n
n
) P Ai = P(Ai
i =1 i =1
. A:

)P(AC) = 1 P(A
. A B:
)P(AB) = P(A) + P(B) P(AB
. A B:
)P(ABC) = P(A) P(AB

)P(A) = P(AB) + P(ABC


. AB )P(A) P(B
:
.
S .


. :

- -

: )(


.
:
) P(A) = P(AB) + P(AB
C
) P(B) = P(AB) + P(A B
C
) P(AB ) = P(A) P(AB
C
) P(A B) = P(B) P(AB
C
) P(AB) = P(A) + P(A B
C

)= P(B) + P(ABC
)= P(ABC) + P(AB) + P(ACB
C
C
) P(A B ) = 1 P(AB

:
0.6 .
:

} { =A

} { = }C { = AC
} { =
P(A) = 0.6 :
:

P(A ) = 1 P(A) = 1 0.6 = 0.4


C

- -

: )(

:
0.6
0.1 .
:

} { =A
} { = B
} { = AB
} { = BC

} { = ABC
P(A) = 0.6 : P(AB) = 0.1
:

P(ABC) = P(A) P(AB) = 0.6 0.1 = 0.5

:
0.25
0.3 0.1
.
:

} { =A
} { = B
} { = AB
- -

: )(

} { = BC
} { = } { = AB
P(A) = 0.25 : P(BC) = 0.3 P(AB) = 0.1
P(B) = 1 P(BC) = 1 0.3 = 0.7
:
P(AB) = P(A) + P(B) P(AB) = 0.25 + 0.7 0.1 = 0.85

:
A 0.35
0.15

A . 0.40 :
. . A
. .

:
:
:
.
.

: A . A
: B .

P(A B) = 0.40, P(B) = 0.15, P(A) = 0.35


P(A B) = P(A) + P(B) P(A B) = 0.35 + 0.15 0.40 = 0.10
P(B ) = 1 P(B) = 1 0.15 = 0.85
C

- -

: )(

:

:
: A

: B 2
:
A, B, AB, AB, AB , A B, (AB)C, AC BC
:
C

} S = {1, 2, 3, 4, 5, 6
. n(S) = 6

}A={2,4,6
n(A) = 3
P(A) = n(A)/n(S) = 3/6
}B= {1, 2
n(B) = 2
P(B) = n(B)/n(S) = 2/6
}AB={2
n(AB) = 1
P(AB) = n(AB)/n(S) = 1/6
AB={1,2,4,6} n(AB) = 4
P(AB) = n(AB)/n(S) = 4/6
C
C
}AB ={4,6
n(AB ) =2
P(ABC) = n(ABC)/n(S) = 2/6
}ACB={1
n(ACB)=1
P(ACB) = n(ACB)/n(S) = 1/6
}(AB)C={3,5
n((AB)C) =2 P((AB)C) = n((AB)C)/n(S) = 2/6
}ACBC={3,5
n(ACBC) =2
P(ACBC) = n(ACBC)/n(S) = 2/6
:
P(AB) = P(A) + P(B) P(AB) = 3/6 + 2/6 1/6 = 4/6
P(ABC) = P(A) P(AB) = 3/6 1/6 = 2/6
P(ACB) = P(B) P(AB) = 2/6 1/6 = 1/6
P( (AB)C ) = 1 P(AB) = 1 4/6 = 2/6
P(ACBC) = P( (AB)C ) = 1 P(AB) = 1 4/6 = 2/6
:
A B :
P(A) = 0.2, P(B) = 0.4, P(AB) = 0.5
:
)P(AB), P(ABC), P(ACB), P(ACBC
:
P(AB) = P(A) + P(B) P(AB) = 0.2 + 0.4 0.5 = 0.1
- -

: )(

P(ABC) = P(A) P(AB) = 0.2 0.1 = 0.1


P(ACB) = P(B) P(AB) = 0.4 0.1 = 0.3
P(ACBC) = P( (AB)C ) = 1 P(AB) = 1 0.5 = 0.5

:


:

= 52
= 26

52
:

) = n(S = 52
52
=
2
A
:
) = n(A = A 26
26
=
2
:

- -

: )(

! 26 26! 26 25 24


n(A) 2 2! 24! 2 24! 26 25
=
=
=
= )P(A
=
= 0.245
n(S) 52 52! 52 51 50! 52 51

! 2 2! 50! 2 50
) (- : Conditional Probability :

A . B

:
A . B

. .
. 100
30 .

.
.
A
. B

) : (:
A B S . P(B)0
A ) ( ) B ( B
) P(A|B :

)P(A B
)P(B

= )P(A|B

- -

: )(

:
. ) P( |B .
. B A:
)P(A B
= )P(B|A
)P(A

. P(A|B) P(B|A) :

. S :
)P(A B) n(A B)/n(S) n(A B
=
= )P(A|B
=
)P(B
)n(B)/n(S
)n(B
. ) AC ( A B :

)P(AC| B) = 1 P(A| B
. :

) P(AB) = P(A) P(B | A


) = P(B) P(A | B
):(-


:

D
40


DC
10

200

130

70

150

95

55

400

235

165

50

. :
: A
: D
- -

: )(

:
. .
..

. .
. .

n(S) = 400 .
P(A) = n(A)/n(S) = 50/400 = 0.125
.
P(D) = n(D)/n(S) = 165/400 = 0.4125
.
.

P(AD) = n(AD)/n(S) = 40/400 = 0.1

P(A | D) = P(AD) / P(D) = 0.1 / 0.4125 = 0.2424

P(A | D) = n(AD)/n(D) = 40/165 = 0.2424


) (- : Independent Events :
A
. B A A . B
) . P(A|B)=P(A A B.
:

A B . S A B

) P(A|B) = P(A
) P(B|A) = P(B
) P(AB) = P(A) P(B

):(-
A D ) (-
:

A D ) (- :
P(A) = 0.125 P(A|D) = 0.2424
- -

: )(

P(AD) = 0.1 P(A) P(D) = 0.1250.4125 = 0.0516


P(D) = 0.4125 P(D|A) = 0.8

:
:

. A B.
. A BC.

. AC B.
. AC BC.

):(-

.
.
:
.
.

} { = A
} { = B
} { = AB

) . P(AB
() : ) ( .

: ) : P(AB) = P(A) P(B | A



. :

20
30
19
29
20 19

= 0.4368
30 29

- -

= )P(A

= ) P(B | A

= )P(AB) = P(A) P(B|A

: )(

20
30

. :

= )P(A

20
= ) P(B | A
30
20 20

= 0.4444
30 30

= )P(AB) = P(A) P(B|A

: :

= )n(S
= )n(AB

P(AB) = n(AB)/n(S) :
n(S) = 30P2 = 30 29
. :
n(AB) = 20P2 = 20 19
n(A B) 20 19
= )P(AB
= 0.4368
=
)n(S
30 29
. :

n(S) = 302 = 30 30
n(AB) = 202 = 20 20
n(A B) 20 20
= )P(AB
= 0.4444
=
)n(S
30 30

):(-
. 4
.
.
:

4 = )n(S
= )n(A
P(A) = n(A)/n(S) :

30
= )n(S
4
- -

: )(

10 20
= )n(A
3 1
= 0.088

10 20

)n(A
3 1
=
)n(S
30

4

= )P(A

) (- : Bayes' Theorem :
.
.
.

.
.
: Total Probability Law
A1,A2,,An ) (
S :

An = S

A i = A1 A2

i =1

Ai Aj = , i j

B S:
)P(B) = P(A1) P(B|A1) + P(A2) P(B|A2) + + P(An) P(B|An
n

) P(A k ) P(B | A k

k =1

:
. ) :( n=3

- -

: )(

) B = (A1B) (A2B) (AnB


n

) (A i B

i =1

(AiB) (AjB) = , i j
}) P(B) = P{(A1B) (A2B) (AnB

)= P(A1B)+P(A2B) + +P(AnB
n

) P(A k B

k =1
n

) P(A k ) P(B | A k

k =1

. ) :( n=3

):(-
.
20% 30%

50% .

1% 4%
. 7%

:

:
- -

: )(

;} { = B
;} {= A1
;} {= A2

;} {= A3

20
1
=)= 0.2 ; P(B|A1
= 0.01
100
100
30
4
=)= 0.3 ; P(B|A2
= 0.04
= )P(A2
100
100
50
7
=)= 0.5 ; P(B|A3
= 0.07
= )P(A3
100
100

= )P(A1

:
3

) P(A k ) P(B | A k

= )P(B

k =1

)= P(A1) P(B|A1) + P(A2) P(B|A2) + P(A3) P(B|A3


= 0.20.01 + 0.30.04 + 0.50.07
= 0.002 + 0.012
+ 0.035
= 0.049

):(-
) (-

- -

: )(

:
) P(A1|B :
)P(A1 B
= )P(A1 | B
)P(B
P(A1 )P(B | A1 ) 0.2 0.01 0.002
=
=
=
= 0.0408
)P(B
0.049
0.049
.
: Bayes' Theorem :

A1,A2,,An ) (
S :

An = S

A i = A1 A2

i =1

Ai Aj = , i j

B S:
) P(A i ) P(B | A i
) P(A i ) P(B | A i
P(Ai | B) = n
; i = 1, 2, , n
=
)P(B
) P(A k ) P(B | A k
k =1

:
) :( n=3

):(-
) (- :
- -

: )(

.
.
.

1.

P(A1) P(B | A1 ) 0.2 0.01 0.002


=
=
=0.0408
0.049
0.049
)P(B

P(A 2 ) P(B | A 2 ) 0.3 0.04 0.012


=
=
=0.2449
0.049
0.049
)P(B

P(A 3 ) P(B | A 3 ) 0.5 0.07 0.035


=
=
=0.7142
0.049
0.049
)P(B

) P(A1) P(B | A1
n

) P(A k ) P(B | A k

=)P(A1|B

k =1

2.
) P(A 2 ) P(B | A 2
n

) P(A k ) P(B | A k

=)P(A2|B

k =1

3.
) P(A 3 ) P(B | A 3
n

) P(A k ) P(B | A k

=)P(A3|B

k =1


.

) (
:

- -

: )(

):(-
. 4 6
8 8 .
.
. .

;} { = B
;} {= A1
:

;} {= A2
6
= 0.6
10
8
= 0.5
=)P(A2) = 0.5; P(B|A2
16
=)P(A1) = 0.5; P(B|A1

- -

: )(

) P(A k ) P(B | A k

= )1. P(B

k =1

)= P(A1) P(B|A1) + P(A2) P(B|A2


= 0.50.6 + 0.50.5 = 0.3 + 0.25
= 0.55
0.5 0.5 0.25
=
= 0.4545
0.55
0.55

) P(A 2 ) P(B | A 2

) P(A k ) P(B | A k

k =1

- -

=)2. P(A2|B